The Effect of Ciplukan Fruit Consumption on Hypertension in Pregnancy - Novita Br Ginting Munthe; Iskandar Markus Sembiring (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Pregnancy hypertension is one of the largest contributors to maternal mortality and needs to be alerted and treated immediately, so that it becomes the center of great attention in improving public health. The next problem is that if this condition is not treated immediately, it can progress to more severe conditions, namely preeclampsia and eclampsia, thereby endangering the mother and unborn baby. The risk to the mother can result in permanent and severe brain damage, heart, kidney and liver damage. Meanwhile, babies are at risk of stillbirth, asphyxia, reduced blood flow to the placenta so that the baby can be born prematurely, nutrition to the fetus is disrupted, resulting in the baby being born with a low weight. The aim of the research was to determine the effect of consuming ciplukan fruit on hypertension in pregnancy. This method uses a